UPAYA PEMERINTAH PROVINSI RIAU DALAM MEWUJUDKAN KETERBUKAAN INFORMASI PUBLIK (STUDI PELAKSANAAN E-GOVERNMENT TAHUN 2014) - Muhammad Jamal; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In organizing the obligatory functions of local governments decentralized in the field of information and communication given the responsibility to the Department of Communications and Information Technology (Diskominfo) Riau Province to implement. In undergoing this responsibility, Diskominfo Riau province are required to be able to take advantage of advances in information technology so that service to the public can be made more transparent and efficient as well as administrative activities of government can be run more easily and cheaply. Utilization of information technology in government agencies called the e -government. The purpose of this study was to determine the extent of implementation of e -government in the province of Riau Diskominfo and any factors that influence it.This study uses the theory of decentralization by Rahardjo Adesasmita who interpret Decentralization is the delegation of responsibility for policy administration, fiscal, and political from the Central Government to Local Government, which is where the organizing decentralization policy in the implementation of mandatory government affairs in the field of communication and information by Diskominfo Riau province needs to develop the concept of e -government should refer to the fourth structure architecture framework on Presidential Instruction No. 3 of 2003 on the National Strategy and Policy Development of E -Government. The fourth structure is access, portal of public services, the organization of information management, and infrastructure and basic applications.The method used in this research is descriptive qualitative data analyisis which through interviews and observations in the field are further analyzed to produce a conclusion. The informant from interviews conducted is of the Diskominfo Riau Province and related parties.Based on the research that has been conducted against the efforts of the Government of Riau Province in realizing Public Disclosure (Study Implementation of E -Government 2014) shows that the implementation of e -government at Diskominfo Riau Province has not run with the maximum and Implementation fourth structure of the architecture framework on Presidential Instruction No. 3 Year 2003 has not been implemented fully because it is influenced by human resources as the main factor.Keywords : Implementation, E-Government, Diskominfo Provinsi Riau